Inhibition of Epstein-Barr Virus Lytic Reactivation by the Atypical Antipsychotic Drug Clozapine - Anderson, Abbie G. (Viruses, 2019)
Epstein–Barr virus (EBV), a member of the Herpesviridae family, maintains a lifelong latent infection in human B cells. Switching from the latent to the lytic phase of its lifecycle allows the virus to replicate and spread. The viral lytic cycle is induced in infected cultured cells by drugs such as sodium butyrate and azacytidine. Lytic reactivation can be inhibited by natural products and pharmaceuticals. The anticonvulsant drugs valproic acid and valpromide inhibit EBV in Burkitt lymphoma cells. Therefore, other drugs that treat neurological and psychological disorders were investigated for effects on EBV lytic reactivation. Clozapine, an atypical antipsychotic drug used to treat schizophrenia and bipolar disorder, was found to inhibit the reactivation of the EBV lytic cycle. Levels of the viral lytic genes BZLF1, BRLF1, and BMLF1 were decreased by treatment with clozapine in induced Burkitt lymphoma cells. The effects on viral gene expression were dependent on the dose of clozapine, yet cells were viable at an inhibitory concentration of clozapine. One metabolite of clozapine—desmethylclozapine—also inhibited EBV lytic reactivation, while another metabolite—clozapine-N-oxide—had no effect. These drugs may be used to study cellular pathways that control the viral lytic switch in order to develop treatments for diseases caused by EBV.